Live foods, live bodies! : recipes for life - Kordich, Jay (Square One Publishers, 2013)
This book is divided into two parts. Part One explores the power of the living enzymes found in fruits, vegetables, and especially greens-- chlorella, green barley, wheatgrass, and more. It explains the many benefits of becoming a vegetarian, and it presents the dos and don'ts of fresh juices -- the very subject that propelled Jay to fame. Part Two puts it all together by laying out what's needed in the living kitchen; offering recipes for fantastic salads, dressings, meals, and drinks; and providing simple yet effective tips for using your new skills to create a better, more fulfilling lifestyle. --amazon.com